Continuous High Frequency Deep Brain Stimulation of the Rat Anterior Insula Attenuates the Relapse Post Withdrawal and Strengthens the Extinction of Morphine Seeking - Chang, Haigang; Gao, Caibin; Sun, Kuisheng; Xiao, Lifei; Li, Xinxiao; Jiang, Shucai; Zhu, Changliang; Sun, Tao; Jin, Zhe; Wang, Feng (Frontiers in Psychiatry, 2020)
Deep brain stimulation (DBS) modulates the neuronal activity in specific brain circuits and has been recently considered as a promising intervention for refractory addiction. The insula cortex is the hub of interoception and is known to be involved in different aspects of substance use disorder. In the present study, we investigate the effects of continuous high frequency DBS in the anterior insula (AI) on drug-seeking behaviors and examined the molecular mechanisms of DBS action in morphine-addicted rats. Sprague-Dawley rats were trained to the morphine-conditioned place preference (CPP, day 1-8) followed by bilaterally implanted with DBS electrodes in the AI (Day 10) and recovery (Day 10-15). Continuous high-frequency (HF) -DBS (130Hz, 150μA, 90μs) was applied during withdrawal (Day 16-30) or extinction sessions. CPP tests were conducted on days 16, 30, 40 during withdrawal session and several rats were used for proteomic analysis on day 30. Following the complete extinction, morphine-CPP was reinstated by a priming dose of morphine infusion (2mg/kg). The open field and novel objective recognition tests were also performed to evaluate the DBS side effect on the locomotion and recognition memory. Continuous HF-DBS in the AI attenuated the expression of morphine-CPP post-withdrawal (Day 30), but morphine addictive behavior relapsed ten days after the cessation of DBS (Day 40). Continuous HF-DBS reduced the period to full extinction of morphine-CPP and blocked morphine priming-induced recurrence of morphine addiction. HF-DBS in the AI had no obvious effect on the locomotor activity and novel objective recognition and did not cause anxiety-like behavior. In addition, our proteomic analysis identified 8 morphine-regulated proteins in the AI and their expression levels were reversely changed by HF-DBS. Continuous HF-DBS in the bilateral anterior insula prevents the relapse of morphine place preference after withdrawal, facilitates its extinction, blocks the reinstatement induced by morphine priming and reverses the expression of morphine-regulated proteins. Our findings suggest that manipulation of insular activity by DBS could be a potential intervention to treat substance use disorder, although future research is warranted.